Pemahaman Guru Bahasa Indonesia SMA di Kabupaten Mesuji terhadap Kurikulum 2013 Edisi Revisi - Munaris Munaris; Bambang Riadi (Universitas Lampung, 2018)
The purpose of this study is to describe the understanding of high school Indonesian teachers in Mesuji District towards the revised edition 2013 curriculum. The method used in this research is descriptive evaluative. The results of questionnaires from 27 respondents indicate that teachers 'understanding of Permendikbud in 2016 number 20 with Good category dominates by almost 50%, teachers' understanding of Permendikbud in 2016 number 21 with Good and Simple dominate by 50% at Permendikbud 2016 number 22 with the category of Good dominate with the amount more than 50%, then the teacher's understanding of Permendikbud year 2016 number 23 with Good category dominate with amount more than 50%. The results can be concluded that the level of understanding of high school Indonesian language teacher in Mesuji District to the curriculum 2013 edition of the revision has been qualified. DOI: http://dx.doi.org/10.23960/aksara/v19i1.pp54-60